Процес вилучення восків із соняшникової олії в присутності ініціаторів кристалізації - Нетреба, Анна Олексіївна; Гладкий, Федір Федорович (Технологический центр, 2013)
Описано процес кристалізації воскоподібних речовин в присутності затравочних матеріалів – ініціаторів кристалізації. Приведено порівняння даного способу кристалізації для систем із різним вмістом воску та різними методами охолодження. Доведена можливість використання інтенсивного охолодження соняшникової олії для виведення воскоподібних речовин.

Despite numerous researches of the crystallization process, the question of its improvement remains open, rather difficult and insufficiently studied. Since this process takes a lot of time and requires careful attention to the observation of its conduc-tion parameters, it becomes necessary to improve the process of crystallization of wax and wax-like substances from oil. This paper proposes a new method of crystallization, namely a method of effective cooling of oil, and filtration improvement by using filtering polymeric fibrous materials. The possibility of the use of crystallization initiators with the formation of large crystals during the traditional winterization process is proved in the paper. It is also shown that the seed materials do not affect the process of effective cooling of oil in any way. However, when using the effective method of cooling, the rate of the extraction of wax-like substances is much higher than when using the traditional method. Besides, the use of fibrous filtering materials simplifies the process of filtering the smallest wax crystals, which are formed under the effective method of cooling. The obtained data will be used for the development of new advanced technologies of winter-ization of sunflower oil.
The process of extraction wax from sunflower oil in the presence of an initiator of crystallization
Keywords: воскоподібні речовини; перліт; фільтрація; процес вінтеризації; wax-like substances; crystallization; crystallization initiators; sunflower oil; perlite; filtration